Effect of longitudinal parameter on the vibration characteristics of unidirectional monolayer glass epoxy composite - Mehta, Vishal; Desai, Saumil (Materials today : proceedings, 2022)
In current scenario, the structures made of composites are becoming popular due to their high stiffness, strength, reinforcement and minimum mass. Till date, various composites have been designed and fabricated. The components/structures made of composites do subject to dynamic loading condition during their operational conditions which results in the failure of the components. Thus, it is significant to understand the vibrational behaviour of the composites based structures under dynamic condition. Here, an analysis is carried out to study the modal characteristics of mono layer glass epoxy based orthotropic composite. The cross section of the glass epoxy is considered as 1000 μm × 100 μm and the fiber orientation is considered along 00. The effect of change in the longitudinal parameter is considered from 1000 μm to 5000 μm to know the vibration characteristic of the composite with two end constraints as follows: (1) Cantilever and (2) Doubly clamped to produce the medium range frequency i.e. kHz to MHz. The results depict that the natural frequency for the doubly clamped configuration is more than the cantilever configuration. The natural frequency decreases with increase in the longitudinal parameter irrespective of the boundary conditions. The results are validated with the available literatures.